Numerical Experiments on PF1000 Neutron Yield - Saw, S. H.; Subedi, D.; Khanal, R.; Shrestha, R.; Dugu, S.; Lee, S. (Springer US, 2014)
Numerical experiments are carried out, using the Lee model code to compute the neutron yield Yn of PF1000 as a function of pressure. Computed results are compared with available published results of neutron yield. Relevant plasma focus properties such as peak discharge current Ipeak, pinch current Ipinch, pinch ion density ni and energy input into the pinch EINP are also discussed as functions of pressures so as to provide correlation of Yn with relevant plasma focus properties over the operational range of pressures.